Fundamental Aspects of Superdisintegrants: A Concise Review. Training According to Kinetic Energy Index and its Impact on Flow and Motor Transport for the Moment of Elevate and Achievement of Long Jump for Youth - Hashem Ali Hassan (Journal of Global Pharma Technology, 2016)
The world has witnessed a dramatic development in the different areas of life nowadays, and this development has been caused by the application of the scientific and modern technological foundations in the sporting field, and despite this development, further research and studies are to be conducted to reveal the best methods and methods for the development of events Sports. Thus, the importance of research is illustrated by the development of the most important scientific solutions through the kinetic Energy index training and its impact on cruise and motor transport at the moment of advancement to achieve the best achievement.  The researchers noted that the preparation of the kinetic energy index exercises did not take place in the application area during the training programs because it has a significant impact on speed development and the kinetic energy index works by determining the intensity of the training according to the mass and speed of the jumper, and that this requires new solutions to help develop Achievement during the technical performance. Therefore, the researchers have developed a motor energy marker exercise and will take into consideration in its flowchart and motor transport at the moment of upgrading for achievement.The Research ObjectivesPreparation of motor energy index drills for young long-jump players.To identify the impact of the exercises with the kinetic energy index in the cruise and motor transport at the moment of upgrading and the long jump to the youth. The Research HypothesisThere is a positive impact of the exercises according to the kinetic energy index in the cruise and motor transport at the moment of upgrading and the long jump to the youth.As for the second chapter, the researchers referred to the training with the kinetic energy Index and its impact on the flow and motor transport at the moment of advancement and the achievement of the long jump of young people, as well as the previous studies that were relevant to the subject matter of the research. The researchers used the training curriculum with the design of the two equal groups (Control and Experimental), which were designed to fit the nature of the research, where the research community, the players of the governorate of Al- Qadisiyah, identified the youth group for the effective long jump of the sports season (2017 – 2018), which number (15) And they are scattered over seven clubs that will officially participate in the championships of the central athletics Federation, selected in the random manner and in the (10) of the shares, which accounted for (66.7%). From the research community, they were evenly distributed to two female officers and experimental groups, and the remaining (5) were selected as a sample of the pilot study. The most important findings were mentioned in conclusions, which showed the moral differences between the pretest and combined tests of the two groups.The Conclusions are followingThere is a positive impact in the use of motor energy marker training in the technical performance and delivery of long jump effectiveness.Kinetic energy Marker training is instrumental in improving the linkage between proximity and elevation to long-term jump.The use of the kinetic energy index in training during training modules leads to the evolution of motor flow of the final step of proximity and preparation for the advancement of Long jump.Keywords: Training, kinetic energy, motor transport, elevate and achievement and long jump.